EVALUASI PERENCANAAN PEMBANGUNAN DESA (RPJMDES DAN RKPDES) - Muhammad Subandi; Musriadi Musriadi (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2020)
The study aims to determine the effectiveness of the village midterm development planning process / RPJMDes and the village government work plan / RKPDes implemented by Sidomukti Village Government, Muara Kaman District, Kutai Kartanegara District, which was evaluated based on Permendagri No 114/2014 on village development guidelines. The study uses an evaluation method with a qualitative descriptive approach, data collection through documentation and interview studies, data analysis using reduction, data presentation, and concluding. The results of the study found that in the preparation of the RPJMDes and RKPDes, the village government had not yet fully implemented the stages as stipulated in Permendagri No 114/2014, in the preparation of the RPJMDes there were 3 stages not carried out namely aligning the direction of district policy, assessment of village conditions, and village deliberations, while in the preparation of the RKPDes there were no indicative ceilings, this was due to the lack of competence of the Village Government officials in preparing the RPJMDes and RKPDes, weak administrative management, and lack of community participation.